Budget implementations in local governments in Uganda; reflections from Kiruhura and Mbarara - Eton, Marus; Sunday, Arthur; Nkamusiima, Dianah (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study focused on the extent of budget implementation in selected local governments in Uganda, focusing on the governance principles of budget implementation, which included participation, transparency, accountability, and gender equity. Research methodology: The research design used was descriptive and analytical to allow for a comprehensive description of budget implementation in the local governments of reference. Data were collected using a structured questionnaire and interview guide. The participants were chosen purposively because they were conversant with the variables under study. Results: The study findings indicated that budget participation increasingly varies from one local government to another due to the low level of awareness among less-educated citizens. There was also a reduction in revenues, a failure of the budget to meet citizens’ needs, and the lack of sufficient time to implement the budget variedly affected budget implementation. Limitations: The study was conducted in only two districts and one city in western Uganda, and their findings make it difficult to generalize the findings. Contribution: This study provides a solid basis for advocating more observation of good governance principles in budget implementation. The study showed that budgeting is a collective responsibility for all, and therefore, transparency and participation are important. It provides valuable insights into budget implementation challenges in Uganda and proposes a workable strategy to respond to the challenges established. It also adds literature on the role of governance, transparency, and participation in budget implementation.